If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 4x(2x^{2}+ -6x + -5) = 0 Reorder the terms: 4x(-5 + -6x + 2x^{2}) = 0 (-5 * 4x + -6x * 4x + 2x^{2}* 4x) = 0 (-20x + -24x^{2}+ 8x^{3}) = 0 Solving -20x + -24x^{2}+ 8x^{3}= 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4x'. 4x(-5 + -6x + 2x^{2}) = 0 Ignore the factor 4.## Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0## Subproblem 2

Set the factor '(-5 + -6x + 2x^{2})' equal to zero and attempt to solve: Simplifying -5 + -6x + 2x^{2}= 0 Solving -5 + -6x + 2x^{2}= 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. -2.5 + -3x + x^{2}= 0 Move the constant term to the right: Add '2.5' to each side of the equation. -2.5 + -3x + 2.5 + x^{2}= 0 + 2.5 Reorder the terms: -2.5 + 2.5 + -3x + x^{2}= 0 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + -3x + x^{2}= 0 + 2.5 -3x + x^{2}= 0 + 2.5 Combine like terms: 0 + 2.5 = 2.5 -3x + x^{2}= 2.5 The x term is -3x. Take half its coefficient (-1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. -3x + 2.25 + x^{2}= 2.5 + 2.25 Reorder the terms: 2.25 + -3x + x^{2}= 2.5 + 2.25 Combine like terms: 2.5 + 2.25 = 4.75 2.25 + -3x + x^{2}= 4.75 Factor a perfect square on the left side: (x + -1.5)(x + -1.5) = 4.75 Calculate the square root of the right side: 2.179449472 Break this problem into two subproblems by setting (x + -1.5) equal to 2.179449472 and -2.179449472.## Subproblem 1

x + -1.5 = 2.179449472 Simplifying x + -1.5 = 2.179449472 Reorder the terms: -1.5 + x = 2.179449472 Solving -1.5 + x = 2.179449472 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = 2.179449472 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = 2.179449472 + 1.5 x = 2.179449472 + 1.5 Combine like terms: 2.179449472 + 1.5 = 3.679449472 x = 3.679449472 Simplifying x = 3.679449472## Subproblem 2

x + -1.5 = -2.179449472 Simplifying x + -1.5 = -2.179449472 Reorder the terms: -1.5 + x = -2.179449472 Solving -1.5 + x = -2.179449472 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = -2.179449472 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = -2.179449472 + 1.5 x = -2.179449472 + 1.5 Combine like terms: -2.179449472 + 1.5 = -0.679449472 x = -0.679449472 Simplifying x = -0.679449472## Solution

The solution to the problem is based on the solutions from the subproblems. x = {3.679449472, -0.679449472}## Solution

x = {0, 3.679449472, -0.679449472}

| 10x^2+5x+8=0 | | 9x^2+9x+8=0 | | 12x^2+5x+10=0 | | 9x^2+21x+12=0 | | -2x^2+4x+12=0 | | 3x^2+10x+8=0 | | -8x^2+8x-2=0 | | X^2-x-2=0 | | 3x^2+x-1=0 | | (8x^4+5x^3-5)-(5x^2-6x+4)= | | 2x^2+10x+12=0 | | (7m^8-5m^3+9m^2+5)+(9m^7+3m^3-4m)= | | X^2-5x-48=0 | | X^2-12x+20=0 | | x^4-4x^3+5x^4-9x^3+2= | | (6x^4y^3+9x^3y^2)+(3x^3y^3-2x^3y^2-7xy)= | | y=x^3+3x^2-9x-8 | | 4x^4+3x^2-1=0 | | kx^2+4x+(5-k)=0 | | 12a^4b^3=0 | | 108x^4+360x^3+447x^2+245x+50=35 | | -35x^2-5x+30=0 | | 12x+2=3x^2 | | 2x^2+3x+5=0 | | (12x^2-3x-8)-(4x^2+5)= | | 5n+6n^4+3n-8n^4+n= | | 3n-2n^4+n+7n^4-2n= | | 12n-2n^4-10n-2n^4+n= | | X^2+16x+42=0 | | x^2+2x-288=0 | | 2x^2+3x-44=0 | | X^2+10x+22=6 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions